Intervention in the Development of Political Advocacy and Election Models: Decision Tree of the Process of Problem-Solving at PERLUDEM - Holqi, Fikri Gali Fernando (STAI Nurul Islam Mojokerto, 2026)
This program aims to develop an election advocacy model at Perludem. This is done by combining sociological principles. This service uses the PAR (Participatory Action Research) method supported by the Social System approach and the Decision Tree of the Process of Problem-Solving intervention. The results of the service have an impact that can enhance the election advocacy model through a social systems approach, using Big Data and Social Network Analysis (SNA), thereby improving the effectiveness, efficiency, and legitimacy of the strategies employed. Through these strategic innovations, Perludem can use the processed data as a strong basis to file lawsuits on election process disputes to Bawaslu (Election Supervisory Body) or election result disputes to the Constitutional Court (MK), strengthening the ability to take and respond to political cases quickly and accurately.